Objective and Subjective Sleep in Rheumatoid Arthritis and Severe Seasonal Allergy: Preliminary Assessments of the Role of Sickness, Central and Peripheral Inflammation - Tamm, Sandra (Nat Sci Sleep, 2021)
INTRODUCTION: Disturbed sleep in inflammatory disorders such as allergy and rheumatoid arthritis (RA) is common and may be directly or indirectly related to disease processes, but has not been well characterized in these patient groups, especially not with objective methods. AIM: The present study aimed to characterize objective and subjective sleep in patients with allergy or RA using sleep diaries, one-channel EEG and actigraphy. It also aimed to investigate if sleep measures were associated with central immune activation, assessed using translocator protein (TSPO) positron emission tomography, as well as cytokine markers of peripheral inflammation and disease-specific symptoms or general symptoms of sickness. METHODS: In total, 18 patients with seasonal pollen allergy, 18 patients with RA and 26 healthy controls were included in the study. Allergy patients and matched controls were assessed twice, in and out of pollen season, and RA patients and controls were assessed once. Sleep was recorded for approximately 1 week at each occasion. RESULTS: Patients with allergy had increased levels of slow-wave sleep during pollen season. In contrast, patients with RA had less SWS compared to healthy controls, while no differences were observed in sleep duration or subjective sleep quality. Across groups, neither proinflammatory cytokines, grey matter TSPO levels nor general sickness symptoms were associated with objective or subjective measures of sleep. Rhinitis, but not conjunctivitis, was correlated to worse subjective sleep and more slow wave sleep in allergy. Functional status, but not disease activity, predicted lower subjective sleep in RA. CONCLUSION: This study tentatively indicates that both patients with allergy and RA display sleep alterations but does not support inflammation as an independent predictor of the sleep disturbance across these patient groups.